Education for Incarcerated Juveniles: A Meta-Analysis. Issue 2 (2nd April 2016) - Steele, Jennifer L.; Bozick, Robert; Davis, Lois M.
ABSTRACT: Based on screenings of 1, 150 manuscripts, we synthesize evidence from 18 eligible studies of educational interventions implemented within juvenile correctional facilities. The studies include 5 intervention categories: remedial academic instruction, computer-assisted instruction, personalized academic instruction, vocational education, and GED completion. Effectiveness is measured in terms of 4 outcomes: academic performance in reading or mathematics, diploma completion, postrelease employment, and postrelease recidivism. Focusing on studies with the strongest basis for causal inference, we find positive and statistically significant effects for computer-assisted instruction in raising reading comprehension, and for personalized learning in improving diploma completion and post-release employment. These findings are driven by large and well-executed randomized trials of Scholastic's Read 180 curriculum and Florida's Avon Park Youth Academy. Despite the limited research base, these studies suggest that it is possible to undertake rigorous research in juvenile facilities about programs that best improve the outcomes of young offenders.